Consent and content: effects of value chain restructuring on work and conflict in highly skilled workforces. (1st October 2012) - Pamela Meil
Abstract : Examinations of the effects of globally distributed work and the creation of new international divisions of labour often focus on quantifiable or structural issues such as challenges to the employment relationship, formal working conditions, contracts, working time, or wage regulation. However, the content of work, however, may also be affected by the restructuring of value chains; but this is difficult to track and to regulate, and may have both objective and subjective dimensions. This paper addresses these issues, drawing on 58 case studies of four different economic sectors in 13 European countries as well an international study on multinational strategies of outsourcing and offshoring to India and China. It analyses the processes leading to segmentation and fragmentation and looks at how employees' consent is obtained for these changes and explanations for the extent to which workers accept the changes brought about by value chain restructuring or find ways to resist them.